2020
DOI: 10.1037/pas0000822
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to assessing emotional understanding.

Abstract: This article describes (a) the origins of, (b) rationale underlying, and (c) preliminary validity evidence for, a new ability measure of emotional understanding (EU), a major component of emotional intelligence. A novel conceptual approach-the empathic agent paradigm (EAP)-provided the theoretical foundation. The EAP results in a veridical, logically defensible scoring key, a major development for the assessment of EI, which otherwise has relied on less defensible approaches. Validity evidence for test score i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…When participants rate their own abilities, their answers may more strongly reflect general self-confidence, narcissism, lack of self-insight, agreeableness, or other theoretically distinct constructs than they reflect their intended construct: actual ability. This is a main reason behavioral tests of such abilities are preferred (e.g., in this journal, see Hellwig et al, 2020).…”
Section: The Fimi Project’s Conceptual Flawsmentioning
confidence: 99%
See 2 more Smart Citations
“…When participants rate their own abilities, their answers may more strongly reflect general self-confidence, narcissism, lack of self-insight, agreeableness, or other theoretically distinct constructs than they reflect their intended construct: actual ability. This is a main reason behavioral tests of such abilities are preferred (e.g., in this journal, see Hellwig et al, 2020).…”
Section: The Fimi Project’s Conceptual Flawsmentioning
confidence: 99%
“…but also on broader theoretical judgments. Given a lack of set thresholds, test developers and evaluators may encounter confirmation biases when evaluating validity: an association strength could be perceived as support for a measure's validity by one scholar while being seen as a sign of invalidity by another scholar (e.g., consider Hellwig et al, 2020: Is a correlation between two behavioral tests of r = .70 evidence that the two tests are or are not redundant with one another?). We encourage researchers to play "Devil's advocate" when evidence is ambiguous.…”
Section: Necessity Of Discriminant Validity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Emotional Ties section of the assessment requires test-takers to match a described scenario with a face realistically displaying the emotion likely triggered in a participant in the situation (Criteria, 2020). Other situational judgment tests with a similar premise include the Changes section of the MSCEIT and the Situational Test of Emotional Understanding, though scoring of these tests remains a challenge (Hellwig, Roberts, & Schulze, 2020). The case study involved 46 volunteer participants who were current public library staff members.…”
Section: Emotify Testmentioning
confidence: 99%
“…She argues that the application of emotional intelligence in everyday decision-making could enhance people's rationality and result in more critical and rational decision-making as well as more effective stress coping. Similarly, Hellwig et al (2020) found that higher emotional understanding resulted in higher reasoning ability and better ability to comprehend and interpret what is going on in situations, which are considered essential abilities that encompass effective and productive coping.…”
Section: A Larger Repertoire Of Coping Strategiesmentioning
confidence: 96%